Design Reviews On Cost Efficiency Of Mosque Foundation Work Of Pekanbaru Qur'an Center Project - Yasri, Desi; Haniza, Sjelly; Susanti, Elvarida (Sekolah Tinggi Teknologi Pekanbaru, 2024)
One of the regional government-owned structures, Pekanbaru Qur'an Centre consists of three building masses: the Qur'an Center Building, the Mosque Building, and the Male and Female Dormitory Buildings. The Covid-19 epidemic caused a substantial delay between planning and execution, which means that cost estimates from 2020 initial planning are not applicable to 2022 construction. The significant time lag between planning and execution resulted in cost escalation of 19.79%, which exceeded contingency costs, which represent a subjective percentage value of 5–10% of the expected final project cost. Since the Qur'an Center Pekanbaru is a one-year project, less than 18 months will pass before it is fully operational. Price modifications are prohibited, as stated in Presidential Regulation Number 16 of 2018 Article 37. Doing a design review is the efficiency step taken to ensure that implementation costs do not vary too much. Efficiency was achieved after Design Review on Detail Engineering Design (DED) of Qur'an Center Project in 2019, based on material and labour costs in 2022, up to 37.48% of the Foundation Work cost, or an efficiency value of up to 3.75% of the mosque building's project standard cost.